Early Cortical Changes in Gamma Oscillations in Alzheimer’s Disease - Klein, Alexandra S.; Donoso, José R.; Kempter, Richard; Schmitz, Dietmar; Beed, Prateep (Frontiers in Systems Neuroscience, 2016)
The entorhinal cortices in the temporal lobe of the brain are key structures relaying memory related information between the neocortex and the hippocampus. The medial entorhinal cortex (MEC) routes spatial information whereas the lateral entorhinal cortex (LEC) routes predominantly olfactory information to the hippocampus. Gamma oscillations are known to coordinate information transfer between brain regions by precisely timing population activity of neuronal ensembles. Here we studied the organization of in vitro gamma oscillations in the MEC & LEC of the transgenic (tg) APP-PS1 mouse model of Alzheimer’s Disease (AD) at 4 – 5 months of age. In vitro gamma oscillations using the kainate model peaked between 30 - 50 Hz and therefore we analyzed the oscillatory properties in the 20 – 60 Hz range. Our results indicate that the LEC shows clear alterations in frequency and power of gamma oscillations early-on in AD as compared to the MEC. The gamma-frequency oscillation slows down in the LEC and also the gamma power in dorsal LEC is decreased as early as 4 – 5 months in the tg APP-PS1 mice. The results of this study suggest that the timing of olfactory inputs from LEC to the hippocampus might be affected early on in AD, resulting in a possible erroneous integration of the information carried by the two input pathways to the hippocampal subfields.